2019
DOI: 10.1155/2019/3702783
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Na+/H+-Exchange Protects Human Colon Cancer Tissue against Intracellular Acidification

Abstract: Increased metabolism accelerates local acid production in cancer tissue. The mechanisms eliminating acidic waste products from human colon cancer tissue represent promising therapeutic targets for pharmacological manipulation in order to improve prognosis for the increasing number of patients with colon cancer. We sampled biopsies of human colonic adenocarcinomas and matched normal colon tissue from patients undergoing colon cancer surgery. We measured steady-state intracellular pH and rates of net acid extrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Although there is little doubt, as detailed throughout this review, that the acidic extracellular microenvironment overall promotes cancer development and progression, it is likely that pH o in tumors can reach levels so low that even the cancer cells become restricted in their functions. Cancer cells usually have higher intracellular pH (pH i ) than normal cells when investigated under similar environmental conditions (8,20,21). Nonetheless, pH i of cancer cells drops substantiallyand to an almost similar extent as that of normal cells-when pH o declines (8,20).…”
Section: Composition Of the Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is little doubt, as detailed throughout this review, that the acidic extracellular microenvironment overall promotes cancer development and progression, it is likely that pH o in tumors can reach levels so low that even the cancer cells become restricted in their functions. Cancer cells usually have higher intracellular pH (pH i ) than normal cells when investigated under similar environmental conditions (8,20,21). Nonetheless, pH i of cancer cells drops substantiallyand to an almost similar extent as that of normal cells-when pH o declines (8,20).…”
Section: Composition Of the Tumor Microenvironmentmentioning
confidence: 99%
“…When the Na + ,HCO 3 − -cotransporter NBCn1, which is responsible for the elevated net acid extrusion capacity in breast cancer tissue compared to normal breast tissue, is genetically disrupted, breast cancer development is delayed, and cell proliferation and tumor growth rate are decelerated (8,57,97). However, the dependency of pH i regulation on HCO 3 − uptake mechanisms is not universal for cancer cells as, for instance, the elevated pH i of human colon cancer tissue relies almost exclusively on accelerated Na + /H + -exchange activity (21). The different transporter dependencies in various cancer forms are in line with the notion that increased capacity for net acid extrusion in cancer cells results from selection for this phenotype rather than upregulation of specific molecular mechanisms.…”
Section: Selection Of Malignant Cancer Cell Populations In the Acidic...mentioning
confidence: 99%
“…Its use in cancer patients is supported by early preclinical studies which demonstrated activity in leukemia and cholangiocarcinoma cells [12,[95][96][97]. Recently, preclinical activity of cariporide has been demonstrated across a broad range of cancer types [98][99][100][101][102][103]. The drug has been shown to inhibit invasion of head and neck squamous cancer [98] and EGFR driven invasion of pancreatric cancer [99].…”
Section: Nhe1mentioning
confidence: 99%
“…Acidic conditions, occurring during GORD, are a key stimulus for the development of BO [6]; those with BO are 40-50 times more likely to develop OAC [42]. Decreased extracellular pH has been implicated in the proliferation of some cancer-derived cell lines (prostate, colon, lung, and breast cancers; pH ranged from 6.0-6.8) [43][44][45][46][47][48]. Extracellular acid (EA) has also been implicated in cancer metastasis in other cell lines (prostate, lung, and murine melanoma cancers; pH ranged from 5.9-6.8) [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Whether acidic extracellular environments result in oncogenesis in OAC, via the development of BO or by other mechanisms, remains unclear. Proposed oncogenic mechanisms include the production of reactive oxygen species (ROS), increased genomic instability, increased proliferation, dysregulation of apoptosis, and increased inflammation [43][44][45][46][47][48][49][50][51][52][53][54][55][56]. Exposure to EA has been linked to ROS production in BO [56].…”
Section: Introductionmentioning
confidence: 99%